GABA Type A receptors expressed in triple negative breast cancer cells mediate chloride ion flux - Bundy, J; Ahmed, Y; Weller, S; Nguyen, J; Shaw, J; Mercier, I; Suryanarayanan, A (Frontiers in Pharmacology, 2024)
Triple negative breast cancer (TNBC) is known for its heterogeneous nature and aggressive onset, limited unresponsiveness to hormone therapies and immunotherapy as well as high likelihood of metastasis and recurrence. Since no targeted standard treatment options are available for TNBC, novel and effective therapeutic targets are urgently needed. Ion channels have emerged as possible novel therapeutic candidates for cancer therapy. We previously showed that GABAA β3 subunit are expressed at higher levels in TNBC cell lines than non-tumorigenic MCF10A cells. GABAA β3 subunit knockdown causes cell cycle arrest in TNBC cell lines via decreased cyclin D1 and increased p21 expression. However, it is not known if the upregulated GABAAR express at the cell-surface in TNBC and mediate Cl -flux. Cl -ions are known to play a role in cellcycle progression in other cancers such as gastric cancer. Here, using surface biotinylation and (N-(Ethoxycarbonylmethyl)-6-Methoxyquinolinium Bromide) MQAE-dye based fluorescence quenching, we show that upregulated GABAAR are on the cellsurface in TNBC cell lines and mediate significantly higher chloride (Cl -) flux as compared to non-tumorigenic MCF10A cells. Moreover, this GABAAR mediated Cl -flux can be modulated by pharmacological agents and is decreased in TNBC cells with GABAA β3 subunit knockdown. Further, treatment of TNBC cells with bicuculline, a GABAAR antagonist reduced cell viability in TNBC cells Overall, these results point to an unexplored role of GABAAR mediated Cl -flux in TNBC.Deleted: . Lastly, p53 levels are elevated in TNBC cells after GABAA β3 subunit knockdown.